Root architecture of apple rootstocks inoculated with arbuscular mycorrhizal fungi - Locatelli, Lucir Maria; Vitovski, Cláudio Assis; Lovato, Paulo Emílio (Pesquisa Agropecuaria Brasileira, 2002)
Root architecture is scarcely considered in plant physiology studies, despite its great importance to plant growth and development. In order to evaluate the behavior of the root systems of two varieties of apple (Malus spp.) rootstock when subjected to mycorrhizal association. Two apple rootstocks were tested: Marubakaido, which is vigorous and roots easily, and M.9, which is dwarfing and poorly rooted. The micropropagated plantlets were transferred to a soil-based substrate and received AMF inoculum, or its non-mycorrhizal biota, before and after a 21-day rooting and weaning period. After 51 and 81 days, the number and length of root axes and of first-, second-, third- and fourth- order roots were evaluated. AMF inoculation before weaning and rooting enhanced the number and length of roots in the Marubakaido rootstock. On the other hand, M.9 rootstock plantlets had their root number and length reduced when mycorrhizal inoculation was performed before the rooting period, as compared to plants receiving the AMF inoculum after the rooting period.
Keywords: inoculation methods; vesicular arbuscular mycorrhizae; micropropagation; plant propagation